Bone mineral density in elite rowers - Lundy, B.; Trease, L.; Drew, M. (2015)
Background: Bone mineral density (BMD) is known to be dependent on the loading pattern associated with a particular sport. High impact sports increases BMD at loaded sites with low impact sports having largely neutral findings [1]. The influence of high level rowing training has not been well explored with relatively small samples within a single category or discipline [2-5].